(untitled) (Baghdad Science Journal, 2011)
A total of 258 voluntary blood donors (males 101; females 157) in the age range of 18-52 yr among males and 18-55 yr among females were examined for Toxoplasma gondii antibodies (IgG), and (IgM) by immunological technique (Enzyme linked Immunosorbant Assay) during the period from March 2009 to April 2010. This study covered a wide range of factors including immunological, age ,sex , place of residence and symptoms that may have a possible relationship with toxoplasmosis. Results presented in this study showed clearly that 38 (14.7%) of individuals participated in this study having IgG Toxoplasma Ab, among those 10 samples (9.9%) were males and 28 samples (17.8%) were females. Moreover, we found the prevalence of IgM seropositivity in the study population to be 5.8% ,as well as, the prevalence of IgM was 1.98 % in males and 8.3% in females. In addition to , the results of current study indicated that the seroprevalence of IgG Toxoplasma antibodies are more than IgM antibodies ,besides , the peak period range of toxoplasma gondii antibodies IgG among males donors was 30 to 39 years, while among female donors, the highest detection of Toxoplasma gondii antibodies IgG was between the ages of 40 to 49. What’s more, the peak age range of Toxoplasma gondii antibodies IgM among males and females donors was 19 to 29 years. In conclusion , Our study showed a high prevalence of T. gondii antibodies in healthy voluntary blood donors. It may be appropriate to include screening test (ELISA) for T. gondii also in the pre transfusion blood testing schedule.